PENGARUH VARIASI FRAKSI VOLUME DAN LAMA PERLAKUAN NAOH PADA KOMPSIT BERPENGUAT SERAT TEBU DENGAN MATRIKS POLYESTER TERHADAP KEKUATAN TARIK DAN IMPACT - sayyid osama; Masdani Masdani; Erwansyah Erwansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Material development is expected to increase efficiency in the field of engineering, judging from the current good material is a material that meets several main standards such as composites. Composite is a material consisting of a mixture of two or more main elements, and composites have a light weight, high strength, corrosion resistance and cheaper price. Presearch aims to find out the effect of variations in volume fraction and length of difference in immersion ofsugarcane fiber using NaOH solution against tensile strength and impact, so that it can be used as potential information about fiber. Sugarcane that can produce a new quality material. The study used variations in volume fractions of 10%, 15% and 20% as well as the length of immersion using NaOH for 30, 60 and 90 minutes. From the tests that have been done, the highest average tensile test value is in the volume fraction of 15% and the length of NaOH treatment of 60 minutes is 36.73MPa and the lowest average value is in the volume fraction of 20% and the length of NaOH treatment is 90 minutes by 21.16 MPa. The maximum average value on the impact test is at a volume fraction of 20% and the length of naOH treatment of 60 minutes is 0.07290 joules / mm², and the average minimum value is in the volume fraction of 10% and the length of naOH treatment is 90 minutes by 0.02849 joules / mm².